The Impact of Changes in Demand and Supply on the Balance of the Supermarket Phase VII of Padang City - Azizah, Hidayatul Putri; Guswandri Putra, Doni; Zefriyenni, Zefriyenni (Green Publisher Indonesia, 2025)
The Impact of Changes in Demand and Supply on the Balance of the Supermarket Phase VII of Padang City